A REVIEW OF RECENT TECHNIQUES IN FACADE ENGINEERING (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Facade Engineering is the art and science of resolving aesthetic, environmental and structural issues to achieve the effective enclosure of buildings. Specialist companies are dedicated to this niche sector of the building industry and engineers operate within technical divisions of facade manufacturing companies. The façade acts as the filter between the climate outside and the conditioned space inside.